Implementasi Sistem Informasi Pendataan Pembayaran SPP pada biMBA AIUEO Karanganyar Kebumen - Arnila Dinar Rahmadani; Ahmad Aftah Syukron (Lembaga Pengembangan Kinerja Dosen, 2025)
This study focuses on implementation of a web-based tuition payment data management information system at biMBA AIUEO Karanganyar Kebumen to improve the efficiency of financial administration. The system is developed to help record payments more quickly, accurately, and systematically, thereby reducing the risk of errors from manual recording. It is also designed to assist administrators in monitoring payment transactions in real-time and increasing the transparency of financial reporting. The Research and Development (R&D) method was employed along with the ADDIE development approach tailored to user needs. Testing was conducted using the Black-Box Testing method, along with distributing questionnaires to unit head unit heads, admins, and students’ parents. The results show that the developed system improves the efficiency of tuition payment management, minimizes input errors, and speeds up access to information. The system’s implementation contributes to greater transparency and effectiveness in the institution’s financial administration.